2020
DOI: 10.3390/app10093040
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Biotechnological Applications of a Novel, Robust, Free-living Chlorococcum (Oophila) amblystomatis Strain Isolated from a Local Pond

Abstract: Bioprospection of novel autochthonous strains is key to the successful industrial-scale production of microalgal biomass. A novel Chlorococcum strain was recently isolated from a pond inside the industrial production facility of Allmicroalgae (Leiria, Portugal). Phylogenetic analysis based on 18S ribosomal ribonucleic acid (rRNA) gene sequences suggests that this isolate is a novel, free-living Oophila amblystomatis strain. However, as our phylogenetic data strongly suggests that the aforementioned taxon belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 50 publications
4
23
1
Order By: Relevance
“…An exploratory analysis of all sequences of the 18S rRNA gene from previous studies targeting Oophila (Correia et al 2020;Kim et al 2014;Muto et al 2017;Nema et al 2019) confirmed that strains assigned to Oophila in these studies belong to two distinct clades within Chlorophyta (Dataset 1; Online Resource 4, Fig. S9).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…An exploratory analysis of all sequences of the 18S rRNA gene from previous studies targeting Oophila (Correia et al 2020;Kim et al 2014;Muto et al 2017;Nema et al 2019) confirmed that strains assigned to Oophila in these studies belong to two distinct clades within Chlorophyta (Dataset 1; Online Resource 4, Fig. S9).…”
Section: Resultssupporting
confidence: 62%
“…Therefore, it is likely that "Clade B" algae are more difficult to culture than (many) "Clade A" algae, and the latter are, therefore, more successfully isolated and cultured (or have a high likelihood to contaminate other isolates, even if present in only very minor proportion in a sample). Two other recent studies are in agreement with this hypothesis: firstly, the DNA metabarcoding study of Jurga et al (2020) only found "Clade B" sequences in numerous North American salamander clutches studied; and secondly, Correia et al (2020) obtained a free-living "Clade A" isolate from a pond in Portugal, which they specifically characterize as robust and with promising growth performance even at industrial scale.…”
Section: Identity Of Oophila Amblystomatissupporting
confidence: 66%
“…Milli-Q water (Synergy, Millipore Corporation, Billerica, MA, USA) was used. Phospholipid internal standards 1,2-dimyristoyl- sn -glycero-3-phosphocholine (dMPC), 1,2-dimyristoyl- sn -glycero-3-phosphoethanolamine (dMPE), 1,2-dimyristoyl- sn -glycero-3-phospho-(10-rac-glycerol) (dMPG), 1,2-dimyristoyl- sn -glycero-3-phospho- l -serine (dMPS), 1,2-dipalmitoyl- sn -glycero-3-phosphatidylinositol (dPPI), N-palmitoyl-D- erythro -sphingosylphosphorylcholine (SM), 1-nonadecanoyl-2-hydroxy- sn -glycero-3-phosphocholine (LPC) were purchased from Avanti Polar Lipids, Inc. (Alabaster, AL), according to the methodology previously described 34 , 35 . DPPH • was purchased from Aldrich (Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%
“…The polar lipidome was determined according to the methodology previously described 34 , 35 . The dried samples were dissolved in CH 2 Cl 2 to a final concentration of 1 ug uL -1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation